2013
DOI: 10.1097/fjc.0b013e31828d0fa3
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-sensing Receptor Cleavage by Calpain Partially Accounts for Altered Vascular Reactivity in Mice Fed a High-fat Diet

Abstract: The Ca-sensing receptor (CaSR) is expressed in endothelial and smooth muscle cells, but its role in regulating vascular reactivity is unclear, as are the effects of disease on CaSR function and expression. We studied vascular reactivity in aortic segments from healthy and diabetic mice, combined with in vitro proteolysis studies and Western blot analyses of CaSR expression in tissue samples. In endothelium-intact aortic rings, extracellular Ca elicited a nitric oxide-dependent relaxation that was attenuated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 40 publications
6
30
0
Order By: Relevance
“…In line with our results of genetic ablation, Loot et al (34) have recently found that pharmacological inhibition of the CaSR attenuated vascular contraction in response to PE and high K ϩ . The congruence of these results of pharmacological CaSR inhibition in WT mice and CaSR ablation in genetically altered mice provides another line of evidence that the VSMCCaSR is indeed directly responsible for the modulation of vascular tone, rather than possible off-target effects of calcilytic drugs (35) or unexpected side-effects of the genetic ablation.…”
Section: Vascular Phenotypesupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our results of genetic ablation, Loot et al (34) have recently found that pharmacological inhibition of the CaSR attenuated vascular contraction in response to PE and high K ϩ . The congruence of these results of pharmacological CaSR inhibition in WT mice and CaSR ablation in genetically altered mice provides another line of evidence that the VSMCCaSR is indeed directly responsible for the modulation of vascular tone, rather than possible off-target effects of calcilytic drugs (35) or unexpected side-effects of the genetic ablation.…”
Section: Vascular Phenotypesupporting
confidence: 92%
“…Indeed, the CaSR expression is found in the vasculature (7,54,59), but a definitive role for this receptor in blood pressure regulation has never been firmly established. In the vascular endothelium, CaSR activation is thought to stimulate nitric oxide (NO) production (34,59) and/or endothelium-derived hyperpolarization (EDH) (54). In rat subcutaneous small arteries, Ca 2ϩ o evokes a biphasic response with contraction followed by dilatation in a concentration-dependent manner (40).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…High-resolution echocardiography analysis was performed using a Vevo2100-high resolution imaging system (VisualSonics, Toronto, Canada) with a 40-MHz transducer (MS-550D) as described. 34 Myograph vascular reactivity analysis of thoracic aortae and mesenteric arteries was performed on a DMT 610M small vessel myograph (Danish Myograph Technology, Aarhus, Denmark) as described 35,36 and analyzed using LabChart 7 software (AdInstruments, Oxford, United Kingdom). Hindlimb perfusion was measured as described.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%